2023
DOI: 10.1253/circrep.cr-23-0038
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Telomere G-Tail Length and Coronary Artery Disease or Statin Treatment in Patients With Cardiovascular Risks ― A Cross-Sectional Study ―

Abstract: Background: The utility of telomere G-tail length to predict coronary artery disease (CAD) remains controversial. CAD results from coronary artery narrowing due to cholesterol and lipid accumulation, augmented by inflammatory cells and other factors. This study explored the significance of telomere G-tail length in suspected CAD patients. Methods and Results: In all, 95 patients with suspected CAD or ≥1 cardiac risk factor underwent coronary computed tomography angiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Patients exhibiting telomere G-tail length shortening are at a heightened risk of cardiovascular events. [42] M Rafiq et al, through a case-control study with meta-analysis, demonstrated an association between LTL and the occurrence of CAD, suggesting its potential utility as a diagnostic and predictive marker for identifying CAD patients. [43] The research conducted by M Xiang et al indicates a correlation between LTL and reduced incidence of coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Patients exhibiting telomere G-tail length shortening are at a heightened risk of cardiovascular events. [42] M Rafiq et al, through a case-control study with meta-analysis, demonstrated an association between LTL and the occurrence of CAD, suggesting its potential utility as a diagnostic and predictive marker for identifying CAD patients. [43] The research conducted by M Xiang et al indicates a correlation between LTL and reduced incidence of coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies in the general population suggest that statins influence hallmarks of aging. For example, statins appear to improve endothelial function through alteration of epigenetic pathways (Liuzzo & Pedicino, 2023 ) and telomere attrition (Nose et al, 2023 ). Interestingly, the American College of Cardiology has recently suggested to consider the impact of geroscience on therapeutic strategies for older adult with cardiovascular disease (Forman et al, 2023 ).…”
mentioning
confidence: 99%